(untitled)
Let (R, m) be a commutative Noetherian local ring, I an ideal of R and M a finitely generated R-module. Let lim_n ^H^i_m(M/I^nM) be the ith formal local cohomology module of M with respect to I. In this paper, we discuss some properties of formal local cohomology modules lim_n ^H^i_m(M/I^nM), which are analogous to the finiteness and Artinianness of local cohomology modules of a finitely generated module. , number=3, journal=Communications in Mathematical Research, year=2021, month=May, pages=230–238